'Forced normalisation' in the neurosurgical era. (8th June 2012) - Shahani, Lokesh
Abstract : The correlation between epilepsy and behavioural disorders is well known. Forced normalisation is a phenomenon where there is worsening of the patient's behavioural disorder when a better seizure control has been obtained. A complication of anti-epileptic treatment worsening the behavioural disorder is sometimes the proposed mechanism. The author presents the report of a young man with temporal lobe epilepsy and poor seizure control in the past 12 years. The patient had comorbid impulse control disorder previously well controlled with medications. MRI demonstrated left mesial temporal sclerosis and intracranial EEG recording located seizure foci in the left medial temporal lobe. The patient underwent left temporal lobectomy for seizure control with partial success. However, after operation, the patient's impulse control disorder worsened and he was involved in physical altercations leading to incarceration. This illustrates a case where partial seizure control was obtained with a surgical procedure, but resulted in worsening of the patient's behavioural disorder.